Condition monitoring with signal processing in wind turbines - (:unkn) unknown (JVE INT LTD, 2011)
Renewable energy sources will come at the beginning of the future energy resources. In particular, wind power is among the most discussed sources in Turkey and all over the world. In this study, a model of the three-blade horizontal-axis wind turbine was designed. Analysis of fault, which may occur as a result of a possible blade deformation, was performed with the model. Comparison is provided between generator rotor speeds and torques for the states of healthy and damaged blades. Continuous wavelet transform (CWT) approach was adopted as the analysis method. The state of the healthy blade and the broken one were clearly identified by means of the CWT.
Keywords: wind turbines; continuous wavelet transform; condition monitoring